2018
DOI: 10.2147/ott.s172149
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen affects cell growth and IGF-1 receptor expression in renal cell carcinoma

Abstract: PurposeBoth obesity and gender are important etiological factors in renal cell carcinoma (RCC) development, suggesting a pivotal role of sex hormone signaling pathway and insulin-like growth factor (IGF) family in RCC carcinogenesis. Here, we aimed to investigate the effect of estrogen on RCC growth and the possible interaction between estrogen/estrogen receptor (ER) signaling pathway and the IGF axis.MethodsER-α and ER-β were detected in four human RCC cell lines. Cells were treated with 17β-estradiol (E2), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Several in vivo and in vitro studies have demonstrated that TNF-α levels correlate with risk of cancer, tumor growth, invasion, and metastasis of RCC (18,21,30). Furthermore, various anti-cancer agents suppress the malignant transformation and tumor progression by interfering with TNF-α-related functions in malignancies including RCC (22,31,32). A clinical trial demonstrated that intravenously injecting infliximab, an anti-TNF-α monoclonal antibody, decreases tumor size and prognosis in RCC patients, suggesting that TNF-α is a putative therapeutic target in such patients (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vivo and in vitro studies have demonstrated that TNF-α levels correlate with risk of cancer, tumor growth, invasion, and metastasis of RCC (18,21,30). Furthermore, various anti-cancer agents suppress the malignant transformation and tumor progression by interfering with TNF-α-related functions in malignancies including RCC (22,31,32). A clinical trial demonstrated that intravenously injecting infliximab, an anti-TNF-α monoclonal antibody, decreases tumor size and prognosis in RCC patients, suggesting that TNF-α is a putative therapeutic target in such patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study based on a randomized double-blind clinical trial and immunity are important for carcinogenesis and malignant invasiveness in multiple cancers (13,14). Moreover, various pro-inflammatory cytokines, including tumor necrosis factor (TNF)-α, tumor necrosis factor (TGF)-β, and interleukin (IL)-6 correlate with malignant transformation and occurrence of adverse events caused by anti-cancer therapies in various types of malignancies (15)(16)(17)(18)(19)(20)(21)(22). Previous reports have shown that RJ regulates the synthesis of these pro-inflammatory cytokines (23)(24)(25).…”
Section: Oral Intake Of Royal Jelly Improves Anti-cancer Effects and mentioning
confidence: 99%
“…Kates et al found that male patients were 1.51 times more likely to develop LNM than females [ 17 ]. This may be attributed to suppression of RCC growth via estrogen/estrogen receptor signaling pathway [ 25 ]. Additionally, we found that higher T stage was closely associated with higher risk of LNM.…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study recently reported that female sex was a significant predictor of poor renal cancer-specific mortality for advanced disease, however, only in postmenopausal period [ 50 ]. In addition, E2 has also been shown to inhibit RCC growth in vitro via an estrogen receptor-ß (ER-ß) dependent pathway [ 51 ]. Finally, hormonal agents such as medroxyprogesterone were initially shown to be active in metastatic RCC, although the response rates reported in various studies were modest, ranging from 7 to 25% [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%